2021
DOI: 10.1111/jors.12531
|View full text |Cite
|
Sign up to set email alerts
|

Too close for comfort? Microgeography of agglomeration economies in the United Kingdom

Abstract: The issue of whether firm productivity is affected by agglomeration externalities is a longstanding area of research.However, the appropriate geographical level to better detect the effects of agglomeration economies and at which level these externalities work is still unclear. Using detailed firm-level longitudinal data on 4927 manufacturing firms in the United Kingdom over the period 2008-2016, we investigate the relation between the microgeography of external agglomeration economies and firm productivity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…Empirical studies in this vein typically find that agglomeration effects operate at different spatial scales. The evidence is consistent with agglomeration effects operating at small spatial scales inside cities, confined to sub-city districts or neighbourhoods (Andersson et al, 2019;Arzaghi & Henderson, 2008;Larsson, 2014;Lavoratori & Castellani, 2021;Rosenthal & Strange, 2003. This type of localized agglomeration effect is typically assumed to reflect knowledge spillovers, since they are more likely than other mechanisms to require close proximity and thus prone to operate at finer spatial scales (Arzaghi & Henderson, 2008;Rosenthal & Strange, 2020).…”
Section: Background and Motivationsupporting
confidence: 63%
See 1 more Smart Citation
“…Empirical studies in this vein typically find that agglomeration effects operate at different spatial scales. The evidence is consistent with agglomeration effects operating at small spatial scales inside cities, confined to sub-city districts or neighbourhoods (Andersson et al, 2019;Arzaghi & Henderson, 2008;Larsson, 2014;Lavoratori & Castellani, 2021;Rosenthal & Strange, 2003. This type of localized agglomeration effect is typically assumed to reflect knowledge spillovers, since they are more likely than other mechanisms to require close proximity and thus prone to operate at finer spatial scales (Arzaghi & Henderson, 2008;Rosenthal & Strange, 2020).…”
Section: Background and Motivationsupporting
confidence: 63%
“…Agglomeration effects operating at small spatial scales may then be under identified. Some recent papers use detailed geographical data and assess the relative roles of industry specialization and industry diversity on the productivity of firms and establishments at different spatial scales (e.g., Andersson et al, 2019;Lavoratori & Castellani, 2021). One finding from this burgeoning literature is that spillovers channelled through industry specialization appear to be more bounded in space than effects of industry diversity.…”
Section: Contributionmentioning
confidence: 99%
“…First, the literature on the geography and attenuation of agglomeration economies and second, the literature on the role of economic proximity (or relatedness) in facilitating spillover effects between firms as well as workers. A main finding from the first set of studies is that there are significant agglomeration effects operating at small spatial scales inside cities, confined to sub-city districts or neighborhoods (Arzaghi and Henderson 2008;Strange 2003, 2008;Andersson, Larsson and Wernberg 2019;Larsson 2014;Lavoratori and Castellani 2020). This type of localized agglomeration effect is typically assumed to reflect some kind of knowledge spillovers, since they are more likely to require close proximity and thus prone to operate at finer spatial scales than other forces that generate agglomeration economies (Arzaghi and Henderson, 2008;Rosenthal and Strange 2019).…”
Section: Background and Contributionmentioning
confidence: 99%
“…The attenuation literature has focused on empirically assessing the distance-decay of localization and urbanization effects as well as of human capital spillovers (e.g. Rosenthal and Strange 2008;Arzaghi and Henderson 2008;Andersson, Klaesson and Larsson 2016;Lavoratori and Castellani 2020) with little attention paid to the influence of various forms of economic proximity beyond industry domains. The literature on economic proximity and relatedness, on the other hand, has not paid sufficient attention to the scale at which agglomeration effects operate and typically use whole regions or cities as their spatial level of analysis (e.g.…”
Section: Background and Contributionmentioning
confidence: 99%
“…Over the past two decades, a growing number of researchers have aimed to identify the factors that encourage or hinder companies in developing and adopting innovations; however, most of the studies dealt with the relationship between innovative local activities and the productive structure or between innovative local activities and workers' skills. Many studies have shown that industrial specialisation (Lavoratori and Castellani 2021;Vlčková and Stuchlíková 2021;Greunz 2004;Mukkala 2004) or diversification (Dzemydaitė 2021;Duranton and Puga 2000;Ouwersloot and Rietveld 2000;Feldman and Audretsch 1999;Usai 1999, 2000) may affect the innovative capacity of the territory with a variety of results that have prevented so far from reaching shared conclusions. Some studies have found a weak association (Van der Panne and Van Beers 2006;Var der Panne 2004) or even any association (Massard and Riou 2002;van Oort 2002;Beaudry et al 2001;Ouwersloot and Rietveld 2000) between propensity for innovation and economic structure.…”
Section: Introductionmentioning
confidence: 99%